Glomerulopatias secundárias à ehrlichiose monocítica canina crônica - Kikuchi, Erica Solange Caetano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Canine monocytic ehrlichiosis (CME), is an infectious disease of high incidence in clinical routine, caused by Ehrlichia canis, an obligate intracellular gram-negative bacterium and transmitted by the tick Rhipicephalus sanguineus. This work aimed to evaluate the histopathological lesions in kidneys and spleen caused by CME, as well as the parameters of serum biochemistry urea, creatinine, albumin and globulin. To this end, 16 dogs showed mean values of urea (90,18mg / dl) and creatinine (1,62mg / dl) were above the normal reference values for dogs; albumin showed values below normal averaging 2.01g / dl, while globulin remained within the average with 3,58g / dl. The histopathological analysis consisted of the evaluation of cortical and medullary region of the kidney and splenic parenchyma. The most prevalent morphological changes were the thickening of the basement membrane, synechia formation, tubular degeneration and necrosis. As for glomerulonephritis the one that presented the highest occurrence was the mesangial type in 62.5% (10/16) of dogs. As for the splenic changes 43.7% (7/16) of the dogs developed hypoplasia of lymphoid follicles, and 87.5% of them (14/16) had plasma accumulation in the parenchyma. The statistical analysis of correlation between the variables, showed positive correlation between the urea concentration and hyperplasia of the glomerular epithelial cells, and also a positive correlation between creatinine and hyperplasia of mesangial cells and tubular dilation; and between the concentration of globulin and infiltrate of plasma cells. Negative correlation was observed for albumin and plasma cell infiltration. In spleen, enlarged lymphoid follicles and urea had positive correlation, whereas albumin and plasma cell infiltrates showed a negative correlation. There was a predominance of mesangial glomerulonephritis, and the plasma cell infiltrate probably plays an essential role in the immunopathology of injuries

A ehrlichiose monocítica canina (EMC), é doença infecciosa de alta incidência na clínica veterinária, causada por Ehrlichia canis, bactéria gram-negativa intracelular obrigatória e transmitida pelo carrapato Rhipicephalus sanguineus. O trabalho teve como objetivo avaliar as lesões histopatológicas em rins e baço causadas pela EMC, assim como os parâmetros da bioquímica sérica, ureia, creatinina, albumina e globulina. Para tanto, 16 cães apresentaram valores médios de ureia (90,18mg/dl) e creatinina (1,62mg/dl) acima dos valores de referência normal para cães; a albumina apresentou valores abaixo do normal com média de 2,01g/dl, enquanto a globulina permaneceu dentro da média com 3,58g/dl. A análise histopatológica constituiu na avaliação da região cortical e medular dos rins e do parênquima esplênico. As alterações morfológicas mais prevalentes foram o espessamento da membrana basal, formação de sinéquias, degeneração e necrose tubular. Quanto às glomerulonefrites a que apresentou maior ocorrência foi a do tipo mesangial em 62,5% (10/16) dos cães. Quanto às alterações esplênicas 43,7% (7/16) dos cães desenvolveram hipoplasia dos folículos linfóides, e 87,5% destes (14/16) apresentaram acúmulo de plasmócitos no parênquima. A análise estatística de correlação entre as variáveis, evidenciou correlação positiva entre a concentração de ureia e hiperplasia de células epiteliais glomerulares, e correlação positiva entre a creatinina e hiperplasia de células mesangiais e dilatação tubular; e entre a concentracão de globulina e o infiltrado de plasmócitos. Correlação negativa foi observada para albumina e infiltrado plasmocitário. Em baço, hipertrofia de folículos linfoides e ureia tiveram correlação positiva, enquanto albumina e infiltrado plasmocitário apresentaram correlação negativa. Houve predomínio de glomerulonefrite mesangial, e o infiltrado plasmocitário parece ter papel...
Glomerulopathies secondary to the chronic canine monocytic ehrlichiosis
Keywords: Glomerulonefrite; Erliquiose; Histopatologia veterinaria; Rins - Doenças; Baço - Doenças; Glomerulonephritis